Elements of Vandalism in Law Number 1 of 2023 Concerning the Criminal Code - Murshal Senjaya (PT FORMOSA CENDEKIA GLOBAL, 2023)
The element of vandalism in Law Number 1 of 2023 concerning the Criminal Code, vandalism is included in the form of delinquency. Crimes related to delinquency are regulated in Article 331. In this article, it is explained that perpetrators of delinquency can be punished with category II fines or as much as IDR 10 million.